Asuhan Keperawatan Gawat Darurat Dengan Non-St-Segment Elevation Myocardial Infarction Di Ruang Instalasi Gawat Darurat (Igd) Pjt Rsup Dr. Wahidin Sudirohusodo - Lenox Daniel Daniel Induk; Mikawati (CV, Akira Java Bulu, 2025)
NSTEMI is a partial occlusion of the coronary artery without involving the entire thickness of the myocardium so that there is no ST segment elevation on the ECG. PURPOSE: this study was to obtain an overview and experience in applying the theory of emergency nursing care with a diagnosis of Non-ST Segment Elevation Myocardial Infarction (NSTEMI) in Mr. D and Mr. A in the emergency room of the integrated heart center of Dr. Wahidin Sudirohusodo Hospital, Makassar. METHOD: the research method used was the Case Study method which was carried out in the emergency room of the integrated heart center of Dr. Wahidin Sudirohusodo Hospital, Makassar. RESULTS: the results of the nursing care assessment in NSTEMI cases found several gaps with the theory and cases where the theory states that in NSTEMI patients, general signs are usually respiratory distress, tachypnea, use of accessory respiratory muscles, dyspnea, depth of breath, respiratory rate, lung expansion, abnormal chest sounds, in cases no signs and symptoms were found that were the same as the theory. ANALYSIS: the results of the analysis of theory and cases found gaps in Breathing. CONCLUSION AND SUGGESTIONS: There are several gaps between cases and theories. Suggestions to the hospital to provide regular training, especially in handling patients with emergency cases to improve knowledge and skills for health workers, especially those in the IGD room of the Integrated Heart Center (PJT)